The Quality Of Life of Patients with Chronic Kidney Disease who Undergo Hemodialysis in RSUD Cilacap - Arik Dian Eka Pratiwi; Maria Immaculata Iwo; Murwiningsih Murwiningsih (Jurnal Kesehatan dr. Soebandi, 2025)
Chronic Kidney Disease (CKD) is one of the mayor health problems in the worldwide. The incidence of CKD continously increase every year, including in Indonesia. Hemodialysis (HD) is the most widely used process of kidney function replacement in Indonesia, including in RSUD Cilacap. This research aim is to study the quality of life (QoL) of CKD patients undergo hemodialysis in RSUD Cilacap using analytic observational design with cross sectional approach. The sampling was carried out using purposive sampling technique. The quality of life of patients was assessed based on WHOQoL-BREF questionnaire consisting of 4 domains i.e., physical, psychological, social relationships, and environment. Other aspects i.e., the CKD causes and therapy adherence were also analyzed. This research employs a descriptive design. The study conducted was univariate to ascertain the distribution of respondent characteristics, which was utilized to evaluate the variance in the quality of life domain among haemodialysis patients. Result showed that hypertension was the main causes of CKD at RSUD Cilacap (59%) beside diabetic mellitus (17%). Before HD, the blood pressure of all patients were in stage 1 hypertension condition with systole: 148.67±29.24 mmHg and dyastole: 80.10±5.47 mmHg. Result of WHOQoL-BREF questionnaire analyses, showed that none of the four domains meet the criteria of good QoL. Generally, based on this data, it can be said that the QoL of CKD patients at RSUD Cilacap were poor categories with score for all domains and a total score (48.96±7.95) below the normal rate. Therapy of hypertension condition of patients before HD with furosemide alone, furosemide+clonidine, and or furosemide+valsartan, could maintain the blood pressure of patients in target value i.e, <140/90 mmHg. Based on those data, it can be concluded that compliance of the patients are important in the improving of QoL of CKD patients who undergo HD in RSUD Cilacap..